(3GbJUGOjGJ GdhWf GdYQHjs - (3GMeO YGQa(B, (3GdYSGas; (3eMehO MSjf GdhGOj(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2010)
(3OQGSI GdehGQO GdHTQjI h GdGbJUGOjI aj bWGY GdRQGYI, GdUfGYI, GdSjGMI, GdJLGQI aj GdhWf GdYQHj eY GdHMK h GdJWhjQ GdJcfhdhLj hGdJcGed GdGbJUGOj GdYQHj(B.s
(3eQGLY U(B.364 (3; edGMb U(B.321s
Keywords: (3GdEbJUGO(B- (3GdHdOGf GdYQHjIs; (3GdGbJUGOs; (3GdJcGed GdEbJUGOjs; (3GdJfejI GdGbJUGOjIs